Old Taoist : the life, art, and poetry of Kodōjin (1865-1944) - Addiss, Stephen, 1935-2022; Chaves, Jonathan; Rimer, J. Thomas (New York : Columbia University Press, 2000)
In the literary and artistic milieu of early modern Japan the Chinese and Japanese arts flourished side by side. Kodojin, the "Old Taoist" (1865-1944), was the last of these great poet-painters in Japan. Portraying this last representative of a tradition of gentle and refined artistry in the midst of a society that valued economic growth and national achievement, this beautifully illustrated book includes a wide selection of his finest poems, paintings, and calligraphy
Frontmatter -- Contents -- Preface and Acknowledgments -- 1. Kodōjin's Life and Art -- 2. Kodōjin's Japanese Poetry -- 3 Kodōjin and the T'ao Ch'ien. Tradition in Kanshi Poetry -- 4. Kodōjin's Chinese Poetry -- A. Note on Kodōjin and the Art and Literature of His Period -- Epilogue -- Notes -- Index.
Includes bibliographical references (pages 165-170) index.
Print version record.
JSTOR
Keywords: Fukuda, Haritsu, -- 1865-1944.; Fukuda, Haritsu, -- 1865-1944; Authors, Japanese -- 20th century -- Biography; Écrivains japonais -- 20e siècle -- Biographies; LITERARY CRITICISM -- Asian -- Japanese; Authors, Japanese; 1900-1999; Biographies; Biographies; Biographies